2012
DOI: 10.1037/a0027268
|View full text |Cite
|
Sign up to set email alerts
|

Classroom emotional climate, student engagement, and academic achievement.

Abstract: The emotional connections students foster in their classrooms are likely to impact their success in school. Using a multimethod, multilevel approach, this study examined the link between classroom emotional climate and academic achievement, including the role of student engagement as a mediator. Data were collected from 63 fifth-and sixth-grade classrooms (N ϭ 1,399 students) and included classroom observations, student reports, and report card grades. As predicted, multilevel mediation analyses showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
529
3
71

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 863 publications
(644 citation statements)
references
References 93 publications
(145 reference statements)
41
529
3
71
Order By: Relevance
“…This finding concurs with other evidence that classroom quality plays a role in students' academic development across populations (Downer et al, 2007;Hamre et al, 2014;Reyes et al, 2012), including Latino students in elementary schools (Downer et al, 2012). Yet, prior studies did not consider individual social processes shown to link with classroom quality, such as teacher-student and peer relationships (Buyse et al, 2009;Gest & Rodkin, 2011).…”
Section: Developmental Differences In the Role Of Relationships In Besupporting
confidence: 91%
See 3 more Smart Citations
“…This finding concurs with other evidence that classroom quality plays a role in students' academic development across populations (Downer et al, 2007;Hamre et al, 2014;Reyes et al, 2012), including Latino students in elementary schools (Downer et al, 2012). Yet, prior studies did not consider individual social processes shown to link with classroom quality, such as teacher-student and peer relationships (Buyse et al, 2009;Gest & Rodkin, 2011).…”
Section: Developmental Differences In the Role Of Relationships In Besupporting
confidence: 91%
“…Given that classrooms are the primary context in which behavioral engagement occurs (Fredricks et al, 2004;Lawson & Lawson, 2013), it is critical to examine the classroom social processes-relationships and interactions among teachers and students-that enhance behavioral engagement Reyes, Brackett, Rivers, White & Salovey, 2012). Two types of supportive relationships have been demonstrated as important social processes to study in relation to behavioral engagement: teacher-student relationships and peer social connections.…”
Section: Supportive Social Processes: Role Of Individual Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Arpiainen, Lackéus, Täks, and Tynjälä 2013;Pekrun, Frenzel, Goetz, and Perry 2007). The emotional level is especially highlighted in social competence development because the ability to recognize and deal with emotions is an important aspect of the competence (Reyes, Brackett, Rivers, White, and Salovey 2012;Rubin, Bukowski, and Parker 2006). Therefore, in the present study, we added a further component into the Integrative Pedagogy model, the emotional level.…”
Section: ---Insert Figure 1 About Here---mentioning
confidence: 99%